When helping is risky: The influence of ethical attributes on consumers’ willingness to buy farmer-assisting agricultural products online - Wu, Jingjing; Wang, Chao; Yan, Yingzheng; Zheng, Qiujin (Frontiers in Psychology, 2022)
Chinese e-commerce platforms have long helped to sell agricultural products through agricultural marketing activities, effectively alleviating the problem of stagnant agricultural products in some areas, and have become a valuable cause-related marketing strategy. The ethical attributes of farmer-assisting agricultural products have unique value compared with other agricultural products. However, the existing research rarely pays attention to the influence of the ethical attributes of farmer-assisting agricultural products on consumers' willingness to buy farmer-assisting agricultural products online. Based on collective efficacy theory and risk perception theory, this study systematically explores the influence mechanism of ethical attributes (symbolic ethical attribute and functional ethical attribute) on consumers' willingness to buy farmer-assisting agricultural products online through three situational experiments. The results show that compared with functional ethical attributes, symbolic ethical attributes have a more positive impact on consumers' willingness to buy farmer-assisting agricultural products online. In addition, it further reveals two mediating pathways of ethical effects (collective efficacy and risk perception) and boundaries (emergency of farmer-assisting events). This study helps to understand the ethical attributes of farmer-assisting agricultural products , and provides some practical suggestions for e-commerce enterprises implementing farmer-assisting marketing communication activities or marketers developing and promoting farmer-assisting agricultural products.